Liver, Spleen, and Kidney Size in Children as Measured by Ultrasound: A Systematic Review - Calle-Toro, Juan S. (J Ultrasound Med, 2019)
Ultrasound is commonly the first-line imaging modality for assessing the pediatric abdomen. An abnormal size of the liver, spleen, or kidneys may indicate disease, but the evaluation is challenging because the normal size changes with age. In addition, published normal value charts for children may vary by population and methods. In this systematic review, we summarized published data on the normal size of the pediatric liver, spleen, and kidneys as measured by ultrasound in which we found similar values across different populations, ages, and sexes.